1999
DOI: 10.1007/s004210050617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of three different types of exercise on components of the inflammatory response

Abstract: It was hypothesized that muscle injury would be greater with eccentric than with all-out or prolonged exercise, and that immune changes might provide an indication that supplements the information provided by traditional markers such as creatine kinase (CK) or delayed-onset muscle soreness. Eight healthy males [mean (SE): age = 24.9 (2.3) years, maximum oxygen consumption (VO2(max)) = 43.0 (3.1) ml x kg(-1) x min(-1)] were each assigned to four experimental conditions, one at a time, using a randomized-block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
4
14

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 30 publications
10
137
4
14
Order By: Relevance
“…The magnitude of increase in IL-6 after exercise is typically intensity dependent (47). In contrast, TNF-␣ generally increases only with high-intensity, long-duration exercise involving a large muscle mass (48). Therefore, it was not surprising that, after exercise in the current study, IL-6 increased without changes in TNF-␣ levels in the men (Fig.…”
mentioning
confidence: 56%
“…The magnitude of increase in IL-6 after exercise is typically intensity dependent (47). In contrast, TNF-␣ generally increases only with high-intensity, long-duration exercise involving a large muscle mass (48). Therefore, it was not surprising that, after exercise in the current study, IL-6 increased without changes in TNF-␣ levels in the men (Fig.…”
mentioning
confidence: 56%
“…The acute changes in IL-6 and TNF-a contrast with other findings following resistance exercise in young healthy individuals. Nieman et al 26 found an increase in plasma IL-6 concentration after 2 h intense resistance training, whereas Brenner et al 27 reported no change in plasma IL-6 or TNF-a concentration following intense circuit training. These differences could be due to variation in exercise protocols and subject characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…an increase in cytokines (such as interleukin 6 (IL6), IL10 and tumournecrosing factor alpha) the metabolic challenge presented by exercise could be viewed as a stress response. The initial interpretation of the exercise-induced increases in white blood cell number was thought to be due to a systemic inflammatory response or due to exercise-induced muscle damage (Brenner et al 1999, Fischer 2006. Interest in the systemic role of cytokine expression has gathered pace since the early observation that the circulating cytokine concentration increases after moderate prolonged exercise (Fischer 2006).…”
Section: The Effect Of Exercise On Cytokine Expressionmentioning
confidence: 99%